Setting a Bad Example: Peer, Parental, and Celebrity Norms Predict Celebrity Bashing. (August 2019) - Ouvrein, Gaëlle; Pabian, Sara; Machimbarrena, Juan Manuel; Erreygers, Sara; De Backer, Charlotte J. S.; Vandebosch, Heidi
The present study investigated the effect of descriptive and injunctive norms of peers, parents, and favorite celebrities on adolescents' negative online behavior toward celebrities. The sample consisted of 1, 255 adolescents (X ¯ a g e = 14.17, SD = 0.47). Adolescents indicated what their peers, parents, and favorite celebrities think of celebrity bashing (injunctive norms) and whether they engage in it (descriptive norms). The adolescents also indicated how often they had participated in negative online behavior toward celebrities and peers. The results revealed that compared with injunctive norms, descriptive norms are better predictors of adolescents' negative online behavior toward celebrities. Focusing on the different role models, the impact of peers was the strongest for both mild and severe forms of celebrity aggression. Moreover, the results showed that adolescents who engage in negative online behavior directed at celebrities are likely to do the same regarding peers.